Bandstop response of microstrip stepped impedance ring with rotational symmetry. Issue 2 (1st January 2013) - Jin, X.H.; Huang, X.D.; Cheng, C.H.
Abstract : The bandstop behaviour of a stepped impedance microstrip ring is studied. The ring is composed of four sections of microstrip line, which are equal in electrical length, but different in impedance. When the impedances of the lines meet the condition of rotational symmetry, a bandstop response could be obtained. At the central frequency of the stopband, the electrical length of the lines is 90°. By tuning the lines' impedances, the bandwidth could be finely adjusted, typically from 0.5 to 40%. Prototypes are designed, fabricated and measured. Good agreements are observed between the measured and the simulated data. The measured data shows that the 3 dB bandwidth is 24%, with a rejection level of −32 dB at the central frequency 1.99 GHz. In addition, the measured matching within the passband is good, as predicted.